Indonesia's geopolitics in connectivity strategy in the implementation of masterplan on asean connectivity 2025 (mpac 2025) - Humaira, Ayesa Nazhifah; Septianti, Annisaa Dwi; Larasati, Vercelli Gipsy; Minasari, Arofah (Universitas Tanjungpura, 2025)
The Master Plan on ASEAN Connectivity 2025 (MPAC 2025) offers ASEAN member states a framework to enhance regional integration via infrastructure, digital innovation, and institutional collaboration. This framework enables Indonesia to leverage connectivity as a geopolitical tool instead of being a passive participant in regional initiatives. This study analyzes Indonesia's utilization of its connectivity agenda to influence ASEAN norms and enhance its regional position, employing geopolitical theory, specifically Rimland Theory, and the notion of soft balancing to assess how geography and infrastructure collaboration bolster strategic autonomy in the context of competition among major powers, including China, Japan, and the United States. The results emphasize initiatives like the Sea Toll Road, the enhancement of Sorong Port, and infrastructure cooperation with ADB and JICA, which not only strengthen domestic integration but also position Indonesia as a norm entrepreneur within ASEAN's regional framework. Indonesia